Alvin and the Chipmunks 2 : The Squeakquel = Alvin ve sincaplar 2 - Thomas, Betty ([S.l.] : Fox 2000 Pictures, 2009)
The world famous singing pre-teen chipmunk trio return to contend with the pressures of school, celebrity, and a rival female music group known as The Chipettes.
Region 2.
3-6.
5-8.
All juvenile.
Languages : Turkish, English, Icelandic.
Subtitles : Turkish, English, Arabic, Croatian, Hindi, Romanian, Tamil, Telugu, Icelandic.
Keywords: Chipmunks -- Movie; Movie -- animated films; Movie -- Fantasy -- Kids